2018
DOI: 10.1002/jocc.12106
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Parent and Peer Relationships, and Identification With Emerging Adulthood Among College Students

Abstract: Relationships are important for college students in terms of their transition to adulthood. The aim of this study was to examine how parent and peer relationship closeness predicted identification with emerging adulthood among 774 undergraduates between the ages of 18 and 20 years. Parent and peer closeness predicted identification with various emerging adult dimensions, but results differed based on gender. Implications are provided for college counselors working with emerging adult college students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
1
9
0
1
Order By: Relevance
“…Regarding the third research question, we hypothesized that each of emerging adults’ perceived levels of individuation would significantly relate to their perceptions of each of their levels of the emerging adulthood features. As noted earlier, numerous studies have found different aspects of the individuation process and parental relationships affect how emerging adults explore identities (Wider et al, 2016) and possibilities (Guan et al, 2016), focus on themselves (Inguglia et al, 2015), feel in-between adolescence and adulthood (Seiter & Nelson, 2011), and experience instability (Schnyders & Lane, 2018).…”
Section: Individuation and The Defining Features Of Emerging Adulthoo...mentioning
confidence: 97%
See 2 more Smart Citations
“…Regarding the third research question, we hypothesized that each of emerging adults’ perceived levels of individuation would significantly relate to their perceptions of each of their levels of the emerging adulthood features. As noted earlier, numerous studies have found different aspects of the individuation process and parental relationships affect how emerging adults explore identities (Wider et al, 2016) and possibilities (Guan et al, 2016), focus on themselves (Inguglia et al, 2015), feel in-between adolescence and adulthood (Seiter & Nelson, 2011), and experience instability (Schnyders & Lane, 2018).…”
Section: Individuation and The Defining Features Of Emerging Adulthoo...mentioning
confidence: 97%
“…For example, emerging adults who perceive their parents to exhibit intrusive qualities (i.e., limiting autonomy, controlling behaviors) are less likely to explore their identities and possibilities, and be self-reliant (Wider et al, 2016). Positive relationships and a sense of connectedness with parents typically contribute to positive identity exploration in emerging adulthood (Schnyders & Lane, 2018). Adolescents and young adults who feel more support from and connectedness with their parents are typically afforded more opportunities to explore possibilities in their careers and other life decisions (Guan et al, 2016), and experience lower levels of instability (Schnyders & Lane, 2018; Wider et al, 2016).…”
Section: Individuation and The Defining Features Of Emerging Adulthoo...mentioning
confidence: 99%
See 1 more Smart Citation
“…As college students develop a sense of identity and transition into their post-college life, peer support and social relationships are critical to overall mental health and a subjective sense of well-being, meaning having an overall positive, happy or desirable feeling about one's life and a sense of quality of life (Menvedev & Landhuis, 2018;Schnyders & Lane, 2018;To & Sung, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Orang tua yang memberikan kemandirian dan dukungan secara seimbang dapat mendorong individu dalam hal eksplorasi dan pengembangan identitas (Luyckx et al, 2007). Sementara itu, bagaimana hubungan individu dengan orang tua akan membentuk keyakinan dan nilai yang diinternalisasi di masa depan (Schnyders & Lane, 2018). Artinya, bagaimana individu berinteraksi dengan orang-orang dan lingkungan di sekitarnya dikorelasikan dengan kondisi hubungan individu dengan orang tuanya.…”
unclassified